Controlled Formation of Carboxymethyllysine in Bone Matrix through Designed Glycation Reaction. (19th October 2021) - Sroga, Grażyna E.; Vashishth, Deepak
ABSTRACT: It has been a challenge to establish a link between specific advanced glycation end products (AGEs) as causal agents of different pathologies and age‐related diseases, primarily because of the lack of suitable in vitro experimental strategies facilitating increased formation of a specific AGE, here carboxymethyllysine (CML), over other AGEs under controlled conditions. CML is of considerable importance to various oxidative stress–related diseases, because in vivo formation of this AGE is connected with cellular oxidative/carbonyl metabolism. The mechanistic implications of CML accumulation in bone remain to be elucidated. To facilitate such studies, we developed a new in vitro strategy that allows preferential generation of CML in bone matrix over other AGEs. Using bone samples from human donors of different age (young, middle‐age, and elderly), we show successful in vitro generation of the desired levels of CML and show that they mimic those observed in vivo in several bone disorders. Formation of such physiologically relevant CML levels was achieved by selecting two oxidative/carbonyl stress compounds naturally produced in the human body, glyoxal and glyoxylic acid. Kinetic studies using the two compounds revealed differences not only between their reaction rates but also in the progression and enhanced formation of CML over other AGEs (measured by their collective fluorescence as fluorescent AGEs [fAGEs]) Consequently, through the regulation of reaction time, the levels of CML and fAGEs could be controlled and separated. Given that the developed approach does not fully eliminate the formation of other uncharacterized glycation products, this could be considered as the study limitation. We expect that the concepts of our experimental approach can be used to develop diverse strategies facilitating production of the desired levels of selected AGEs in bone and other tissues, and thus, opens new avenues for investigating the role and mechanistic aspects of specific AGEs, here CML, in bone. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.